Ordinary wastewater treatment in Costa Rica: technological profile and sustainability prospects - Mora, Erick Centeno (2023)
In Costa Rica, there are significant challenges regarding wastewater treatment. This study evaluated the management of municipal wastewater in Costa Rica, with emphasis on the technological profile, the use of anaerobic systems, and the recovery of generated by-products. A mixed approach was used, combining secondary information from databases, expert consultations, and participatory workshops. It was found that the majority of existing systems work with activated sludge and direct discharge to receiving bodies. Additionally, significant gaps were identified for the implementation of anaerobic systems for wastewater treatment. From a technical standpoint, the lack of training and confidence in designing and operating these systems was noted, along with the relevance of controlling the treatment of emerging contaminants. From an economic standpoint, the lack of financial sustainability of projects, low capacity for user payment, and lack of incentives or tiered tariff systems were identified. Within institutional gaps, the main issue was the need for clearer sectoral leadership and avoiding duplication of functions. All the above requires robust and clear regulations that allow for innovation in the systems to be implemented. Finally, it was found that for the circular economy principle to become a reality, cultural change is required, and the paradigm that wastewater is only meant for disposal must be changed.